Assessment Of The Association Of Algerian Muslim Scholars’ Contribution In The Promotion Of Education - Rahmani, Mokhtaria (جامعة الوادي - University of Eloued, 2022)
enlightenment. This is why they promoted the proliferation of superstition. However, the efforts of the Association of Algerian Muslim scholars (AAMS), counteracted those plans and launched an educational system that strove for the education of Algerians. The intent of this paper is to explore the nature of this system and canvass the extent of its success, specifically in instituting a schooling system. A descriptive-analytical method is used to scrutinize both primary and secondary sources. The investigation tackles three elements, namely colonial education in Algeria before the advent of the AAMS, the birth of the Association, and the educational system of the AAMS. The findings invoke the AAMS’s leaning on a modern free educational system, through the medium of Arabic, that made emulation, evaluation, communication, and gender equity in educational opportunities its prime concern. كانت االمجهودات التعليمية الاستعمارية الفرنسية في الجزائر موجهة لإعاقة اللغة العربية كوسيلة لنشر الإسلام والتنوير. هذا هو السبب في أنهم روجوا لانتشار الخرافات. ومع ذلك ، فإن جهود جمعية العلماء المسلمين الجزائريين تصدت لتلك الخطط ، وأطلقت نظامًا تعليميًا لتعليم الجزائريين. الهدف من هذا المقال هو استكشاف طبيعة هذا النظام واستطلاع مدى نجاحه ، وتحديداً في إنشاء نظام تعليمي. تم استخدام أسلوب تحليلي وصفي للتدقيق في كل من المصادر الأولية والثانوية . ويتناول التحقيق ثلاثة عناصر ، وهي التعليم الاستعماري في الجزائر قبل ظهور الجمعية ، نشأة الجمعية ، ونظامها التعليمي . أظهرت النتائج لجوء الجمعية إلى نظام تعليمي مجاني حديث ، من خلال اللغة العربية ، والذي جعل المحاكاة والتقييم والتواصل والمساواة بين الجنسين في الفرص التعليمية همها الأساسي
مقال
Keywords: Association of Algerian Muslim Scholars ; educational system ; Arabic language ; emulation ; evaluation